2020
DOI: 10.1111/fwb.13671
|View full text |Cite
|
Sign up to set email alerts
|

West Asian colonisation of topmouth gudgeon, Pseudorasbora parva (Teleostei: Gobionidae): Genetic admixture at the crossroad of Europe and east Asia

Abstract: Iran is a major freshwater fish diversity hotspot in the Middle East, and is an important zoogeographical area in west Asia, acting as the crossroads and dispersal corridor between several major biogeographical realms of the world. The topmouth gudgeon, Pseudorasbora parva was first recorded in Iran on 6 May 1991 in the Caspian Sea basin and is now widely distributed across the country. Despite widespread distribution in the Iranian inland waters, its invasion history and genetic background remain unknown. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…Iran showed a pattern of assignment similar to that of the Japanese admixture in nuclear markers between endemic and Chinese populations, potentially explaining why it was not possible to disentangle China and Japan as putative sources. In line with our results, a recent study (Ganjali et al 2020), based on two mtDNA markers, identified three Iranian matrilineal haplotypes belonging to two distinct lineages, an older Japanese lineage and a Chinese lineage, corresponding to a recent natural dispersal from Azerbaijan. They also highlighted an admixture of highly divergent Japanese and Chinese lineages (Hardouin et al 2018).…”
Section: Origins Of Invasion: Admixture and Multiple Introductionssupporting
confidence: 91%
“…Iran showed a pattern of assignment similar to that of the Japanese admixture in nuclear markers between endemic and Chinese populations, potentially explaining why it was not possible to disentangle China and Japan as putative sources. In line with our results, a recent study (Ganjali et al 2020), based on two mtDNA markers, identified three Iranian matrilineal haplotypes belonging to two distinct lineages, an older Japanese lineage and a Chinese lineage, corresponding to a recent natural dispersal from Azerbaijan. They also highlighted an admixture of highly divergent Japanese and Chinese lineages (Hardouin et al 2018).…”
Section: Origins Of Invasion: Admixture and Multiple Introductionssupporting
confidence: 91%